BIOREMEDIATION OF HEAVY METAL CONTAMINATED SOILS AND ITS IMPACT ON WHEAT GROWTH AND PHYSIOLOGICAL HEALTH - Jyoti; Nanda, Abhijeeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the potential of microbial bioremediation in improving soil quality and promoting wheat growth in areas contaminated with heavy metals. Soil samples from heavily contaminated sites in Haryana, India, were treated with native microbial consortia and engineered microbial strains for bioremediation. The impact of soil remediation on wheat (Triticum aestivum) growth was evaluated by measuring growth parameters, chlorophyll content, and antioxidant enzyme activities. The results showed that bioremediation significantly enhanced wheat growth, with notable improvements in shoot length, root length, total biomass, and chlorophyll content. The findings highlight the potential of microbial bioremediation as a sustainable approach to restore contaminated soils and enhance agricultural productivity.